(15)N MRI of SLIC-SABRE hyperpolarized (15)N-labelled pyridine and nicotinamide - Svyatova, Alexandra (Chemistry, 2019)
Magnetic Resonance Imaging (MRI) is a powerful non-invasive diagnostic method extensively used in biomedical studies. A significant limitation of MRI is its relatively low signal-to-noise ratio, which can be increased by hyperpolarizing nuclear spins. One promising method is Signal Amplification By Reversible Exchange (SABRE), which employs parahydrogen as a source of hyperpolarization. Recent studies demonstrated the feasibility to improve MRI sensitivity with this hyperpolarization technique. Hyperpolarized (15)N nuclei in biomolecules can potentially retain their spin alignment for tens of minutes, providing an extended time window for the utilization of the hyperpolarized compounds. In this work, we demonstrate for the first time that radio-frequency-based SABRE hyperpolarization techniques can be used to obtain (15)N MRI of biomolecule 1-(15)N-nicotinamide. Two image acquisition strategies were utilized and compared: Single Point Imaging (SPI) and Fast Low Angle SHot (FLASH). These methods demonstrated opportunities of high-field SABRE for biomedical applications.